Affective Animals: Transspecies Encounters in Modern British Animal Writing - Huggan, Graham (Humanimalia, 2020)
British animal writing is among the most popular of its kind in the world, including such household names as Williamson, Maxwell, and Durrell. It is hardly reassuring, however, for either younger or older readers. Drawing on some recent examples mostly written after the Second World War, this essay makes the case for modern British animal writing as a genre less likely to reveal our capacity to reach out to nonhuman others than to comment –– sometimes devastatingly –– on the modern dissociated sensibility: our otherness to ourselves.